PENGARUH SUKU BUNGA KREDIT DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP PENYALURAN KREDIT PERBANKAN BANK UMUM DI RIAU - Suci Tesa Fitria; Anthony Mayes; Darmayuda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Riau is a province that is actively regional development. The development aims to create a society that is advanced and independent Riau. The conditions need support from the banks, particularly in terms of lending. The purpose of this study was to determine lending rates and gross domestic regional product of the loan portfolio of commercial banks in Riau. The results showed that mortgage interest rates and gross domestic regional product significantly influence the commercial bank lending in Riau. Partially, variable lending rates both working capital loans, investment loans, and consumer loans, has a negative and not significant effect on total loans in Riau. While gross domestic regional product variable has a positive and significant impact on working capital loans, investment credit and consumer loans,. Simultaneously, the variable mortgage interest rates and gross domestic regional product has a significant effect on bank lending of commercial banks in Riau.Keywords: Lending Rates, Gross Domestic Regional Product, Commercial Banks, Riau.